Plany życiowe i marzenia mieszkańców domów pomocy społecznej dla osób z niepełnosprawnością intelektualną - Tylewska-Nowak, Beata (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
Adult residents of residential homes for people with intellectual disabilities are a group of people, who are rarely asked for opinion, even i fit comes to their own case. What are they future plans and wishes, what do they dream about, how often do they do it and what is the characteristic of those thoughts. In this article I present an attempt to annalize those topics using material I colected through narrative and nondirective interviews.